2020
DOI: 10.1002/ece3.6413
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiomes of sympatric Amazonian wood‐eating catfishes (Loricariidae) reflect host identity and little role in wood digestion

Abstract: Neotropical wood‐eating catfishes (family Loricariidae) can occur in diverse assemblages with multiple genera and species feeding on the same woody detritus. As such, they present an intriguing system in which to examine the influence of host species identity on the vertebrate gut microbiome as well as to determine the potential role of gut bacteria in wood digestion. We characterized the gut microbiome of two co‐occurring catfish genera and four species: Panaqolus albomaculatus , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
1
7
0
1
Order By: Relevance
“…The analysis of gut microbiota among stickleback populations performed by Smith et al (2015) attributed the bacterial differences mainly to host genotype, although they were not able to discriminate between long term and transient inhabitants. Similar results were found recently in the gut microbiota of sympatric wood-eating catfishes (McCauley et al 2020) and between the skin and gut microbiota of three different species of fishes in Amazonian rivers, where results suggest a strong correlation with host ancestry (Sylvain et al 2020). In opposition, Bledsoe et al (2018) found that shared environment could overcome the differences in the gut microbiota imposed by the host genotype, a proposal that is also supported in other studies such as that performed by Riiser et al, (2020) who found that the gut microbiota between different fish species in Norway is driven by water temperature and diet and not with host selection.…”
Section: Discussionsupporting
confidence: 86%
“…The analysis of gut microbiota among stickleback populations performed by Smith et al (2015) attributed the bacterial differences mainly to host genotype, although they were not able to discriminate between long term and transient inhabitants. Similar results were found recently in the gut microbiota of sympatric wood-eating catfishes (McCauley et al 2020) and between the skin and gut microbiota of three different species of fishes in Amazonian rivers, where results suggest a strong correlation with host ancestry (Sylvain et al 2020). In opposition, Bledsoe et al (2018) found that shared environment could overcome the differences in the gut microbiota imposed by the host genotype, a proposal that is also supported in other studies such as that performed by Riiser et al, (2020) who found that the gut microbiota between different fish species in Norway is driven by water temperature and diet and not with host selection.…”
Section: Discussionsupporting
confidence: 86%
“…This, in addition to digestive enzyme activity profiles and fermentation levels in the gastrointestinal tract, suggests that wood‐eating armored catfishes are consuming detritus rather than wood (German 2009). Further, the microbiomes of wood‐eating loricariids suggest minimal digestion of wood, meaning these fishes may rely on microbes in the environment to degrade wood fiber (McCauley et al 2020). This further supports our hypothesis that jaw shape in armored catfishes is associated with the surface type they are feeding on and items that are assimilated are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing gut contents could be another possibility for better establishing what loricariids feed upon, but loricariids consume mostly indigestible material. For example, although wood-eaters consume wood, they are not likely digesting it [64][65][66]. Determining what is in the gut of a loricariid may not be reflective of what loricariids are digesting and assimilating.…”
Section: And S3 Fig)mentioning
confidence: 99%
“…These taxa have very different teeth suggesting that changing teeth with similar jaw morphologies may allow for accessing different food items. Yet, determining diet type remains a problem with loricariids due to indistinguishable gut contents and the quick gut passage rates that limit the important dietary material in the intestinal track [64][65][66].…”
Section: And S3 Fig)mentioning
confidence: 99%